Overview of fuel inventory in JET with the ITER-like wall. (17th July 2017) - Widdowson, A.; Coad, J.P.; Alves, E.; Baron-Wiechec, A.; Barradas, N.P.; Brezinsek, S.; Catarino, N.; Corregidor, V.; Heinola, K.; Koivuranta, S.; Krat, S.; Lahtinen, A.; et al.
Abstract: Post mortem analyses of JET ITER-Like-Wall tiles and passive diagnostics have been completed after each of the first two campaigns (ILW-1 and ILW-2). They show that the global fuel inventory is still dominated by co-deposition; hence plasma parameters and sputtering processes affecting material migration influence the distribution of retained fuel. In particular, differences between results from the two campaigns may be attributed to a greater proportion of pulses run with strike points in the divertor corners, and having about 300 discharges in hydrogen at the end of ILW-2. Recessed and remote areas can contribute to fuel retention due to the larger areas involved, e.g. recessed main chamber walls, gaps in castellated Be main chamber tiles and material migration to remote divertor areas. The fuel retention and material migration due to the bulk W Tile 5 during ILW-1 are presented. Overall these tiles account for only a small percentage of the global accountancy for ILW-1.